(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
TThe aim of this paper is to investigate a process of social modernization of the People’s Republic of China and the Republic of Kazakhstan. With the help of a comparative analysis of the processes of modernization in China and Kazakhstan, the author showed the realization of social modernization in these countries. The author also considered the programs and reforms in the social sphere of the two countries.he aim of this paper is to investigate a process of social modernization of the People’s Republic of China and the Republic of Kazakhstan. With the help of a comparative analysis of the processes of modernization in China and Kazakhstan, the author showed the realization of social modernization in these countries. The author also considered the programs and reforms in the social sphere of the two countries.